The effects of secondary treated wastewater on vegetable growth under soil and soilless culture / Shahrul Azwan Shakrani - Shakrani, Shahrul Azwan (2014)
This study highlighted the effects of secondary treated wastewater to macronutrients and trace elements availability in mustard greens grown under soil and soilless culture. Higher macronutrients and trace elements concentrations were found in FSTW as compared to BSTW suggested seasonal variations and treatment system efficiency affected wastewater quality. The application of FSTW and BSTW for irrigation has significantly contributed to soil fertility and toxicity with most of macronutrients, micronutrients and beneficial elements being absorbed by plants for physiological activities otherwise interacted in soil particularly trace elements. Besides, higher macronutrients and trace elements level were measured in plant grown under soilless as compared to soil culture suggested soil media as good filter for potentially toxic elements removal while soilless media have a greater metal tolerance. Meanwhile, the DIM and HRI conducted shown children were highly exposed to risk as compared to adults suggested that former may be vulnerable towards macronutrients and trace elements due to influence of assumed body weight and consumption rates. Nevertheless, the HRI indicated values was <1 and concluded plants are safe to be consumed by adults and children. In addition, higher plants heights, diameter and number of leaves were observed in plant grown under soil as compared to soilless culture suggested that role of soil as trace elements filter for plant uptake. Hence, the application of FSTW and BSTW has a potential application to irrigation crops with continuous monitoring in order to assess possible detrimental effects to human and environmental resulted from short and long term irrigation